Effect of Fortification with Different Starches on Starch Digestibility, Textural and Ultrastructural Characteristics of Sweet Potato paghetti - Menon, Renjusha; Padmaja, G.; Sajeev, M.S.; Sheriff, J.T. (JOURNAL OF ROOT CROPS, 2013)
The effect of fortification with various sources of starch such as banana, lentil, black gram and sweet potato in reducing the in vitro starch digestibility and glycaemic index of sweet potato spaghetti was investigated at Central Tuber Crops Research Institute, Thiruvananthapuram, India. Swelling index and cooking loss were more for the starch-fortified spaghetti than the control spaghetti. Among the starches, highest cooking loss was obtained for 10% lentil starch fortified sample. Crude protein content was higher for black gram and sweet potato starch fortified spaghetti. In vitro starch digestibility increased very slowly from 20-120 min, for the fortified samples compared to the unfortified controls. Accordingly, the rapidly digestible starch (RDS) was less and resistant starch (RS) was more for the starch-fortified samples. The estimated glycaemic index (EGI) was low for the spaghetti fortified with banana, lentil and sweet potato starches at 5 and 10% levels, indicating that these could be considered as low glycaemic foods. Firmness of cooked spaghetti was maximum for black gram starch fortification, while toughness was the maximum for lentil starch based cooked samples. Ultrastructural studies showed starch gelatinization and leaching with diffused granular shape for most spaghetti samples. Whey protein concentrate promoted starch-protein network formation leading to slow starch digestibility.